Meteorological data from Tarfala Ridge, weather station - Tarfala Research Station (Stockholm University, 2020)
Automatic weather station data from locations within the distributed Swedish research infrastructure SITES. Check preview or file for the specific parameters included at this location. Data has been quality controlled and cleaned from outliers and other events producing unrealistic data. Gaps have not been filled.
Tarfala Research Station (2020). Meteorological data from Tarfala Ridge, weather station, 2020-01-01–2020-09-03 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/NveLomH8r0jQoL6-cMeduohF
Keywords: Tarfala Research Station; Atmospheric radiation; Humidity; Precipitation; Surface Winds; Time instant; Time instant; Air temperature; Air temperature; Relative humidity; Relative humidity; Incoming shortwave radiation; Incoming shortwave radiation; Wind speed; Wind speed; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap